ҚАРАҚАЛПАҚ ТИЛИНДЕГИ ӨЗЛЕСТИРИЛГЕН СӨЗЛЕРДИҢ ҚУРЫЛЫСЫ ҲАҚҚЫНДА - Темирханова, Г.У. (FAN va JAMIYAT, 2023)
This article examines the structural differences of borrowed words in the Karakalpak language, and also interprets lexical and morphological borrowings and their penetration into the Karakalpak language. Borrowed words are those words that entered the Karakalpak language without translations, but with meanings and explanations from foreign languages.